THE ROLE OF PALM OIL WORKERS IN ENSURING LIVELIHOOD SECURITY AND SOCIO-ECONOMIC RESILIENCE: A LITERATURE REVIEW ON WELFARE, SOCIAL JUSTICE, AND SUSTAINABLE DEVELOPMENT IN THE PLANTATION SECTOR - Yustinus Lambang Setyo Putro; Siti Nur Azizah; Gunawan Widjaja; Dyah Ersita Yustanti (Adisam Publisher, 2025)
This study examines the role of palm oil workers in ensuring livelihoods and socio-economic resilience through a literature review focusing on aspects of welfare, social justice, and sustainable development in the palm oil plantation sector. This study highlights the importance of welfare, including decent income, access to social services, and protection of workers' rights as the main foundations for strengthening socio-economic resilience. Furthermore, this study emphasises the role of social justice in ensuring the fair distribution of benefits and opportunities, as well as the need for environmentally conscious plantation management to support sustainable development and ecosystem balance. Through a holistic and participatory approach, this study concludes that strengthening the active role of the palm oil worker community is vital to creating an inclusive, equitable, and sustainable plantation industry for the sake of the sustainability of life and the environment for future generations.